Contemporaneous crust-derived I- and S-type granite magmatism and normal faulting on Tinos, Delos, and Naxos, Greece: constraints on Aegean orogenic collapse - Lamont, TN; Roberts, NMW; Searle, MP; Gardiner, NJ; Gopon, P; Hsieh, Y-T; Holdship, P; White, RW (Geological Society of America, 2023)
Granitoids of varying mineralogy are exposed on the Cycladic islands of Greece; they include both hornblende-bearing I-type granites and garnet ± muscovite–bearing S-type granites, suggesting heterogeneous magma sources. In this contribution, we present new field observations, major- and trace-element geochemistry, Sr-Nd isotopes, and U-Pb geochronology of granitoids from Tinos, Delos, and Naxos that provide insight into these magma sources, along with the timing of adjacent extensional structures. I-type (biotite and hornblende-biotite) granites have initial 87Sr/86Sr = 0.70956–0.71065 and εNd(t) = −6.3 to −9.3, and S-type (garnet ± tourmaline-muscovite) leucogranites have overlapping initial εNd(t) = −7.5 to −10.1, with initial 87Sr/86Sr values overlapping as well as extending to higher values (0.70621–0.73180). These isotope signatures are comparable to those of the Variscan-age Cycladic basement, but not the Hellenic arc. We suggest that both I- and S-type granites were derived via crustal anatexis of variable sources, dominantly metaigneous and metasedimentary, respectively, during the climax of Barrovian metamorphism between ca. 17 and 12 Ma, and critically, they are not related to the Hellenic subduction zone. I-type granitoids were likely derived from dehydration melting of igneous Variscan- or Cadomian-aged basement protoliths, whereas S-type leucogranites formed by muscovite dehydration melting of sedimentary protoliths. Top-to-the-(N)NE shear zones on Naxos and Tinos were active from ca. 20 to 15 Ma and are folded and cut by later low- and high-angle normal faults. S-type leucogranites at Livada Bay, Tinos, dated at ca. 14 Ma, are cut by domino-style normal faults, placing a maximum age on the timing of extension. This is similar to ca. 15–14 Ma dates from NNE-SSW horizontally boudinaged S-type granites on Naxos. We propose that the concurrent intrusion of both I- and S-type granitoids with the onset of normal faulting marked the transition from an overall compressional to an extensional stress field associated with orogenic collapse at ca. 15 Ma.